2016
DOI: 10.2500/aap.2016.37.3913
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of childhood eczema and the effect of indoor environmental factors: Analysis in Hispanic and non-Hispanic white children

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…For example, variants at chromosome 17q21 show strong associations on exposure to maternal smoking [83], however, the interaction between air pollution and genes for incident asthma show mixed results in a number of studies [76]. Likewise, the manifestation of atopic dermatitis (AD) in children appears to be on the rise in many countries, and the potential environmental triggers may be dependent on ethnic (race, culture and place of birth) differences, where typically Blacks and non-Hispanic whites show higher AD rates [84,85]. Filaggrin, a filament-associated protein, has been identified most recently as associated with a host of allergic diseases, including AD and asthma [85].…”
Section: Approachmentioning
confidence: 99%
“…For example, variants at chromosome 17q21 show strong associations on exposure to maternal smoking [83], however, the interaction between air pollution and genes for incident asthma show mixed results in a number of studies [76]. Likewise, the manifestation of atopic dermatitis (AD) in children appears to be on the rise in many countries, and the potential environmental triggers may be dependent on ethnic (race, culture and place of birth) differences, where typically Blacks and non-Hispanic whites show higher AD rates [84,85]. Filaggrin, a filament-associated protein, has been identified most recently as associated with a host of allergic diseases, including AD and asthma [85].…”
Section: Approachmentioning
confidence: 99%
“…Current epidemiological studies show inconsistent associations of breastfeeding duration, maternal gestational smoking with eczema, when investigated separately [3, 12, 1418]. None of the studies have yet investigated the interaction of maternal gestational smoking and duration of breastfeeding in relation to eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Eczema is a chronic relapsing inflammatory skin disease characterized by a disrupted epidermal barrier [1, 2] with a lifetime prevalence ranging from 16–20% in the UK and US [3, 4], which is further increased in the developing countries [5]. Characteristically, an early onset eczema often progresses to other allergic diseases [6–9], a phenomenon known as atopic march [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 9 demonstrated that exposure to elevated carbon monoxide levels during infancy increases the risk of development of allergic rhinitis and of atopic dermatitis symptoms in South Korean children. Kim et al 10 investigated the effects of ethnicity and environmental exposures on eczema in Hispanic white and non-Hispanic white children who participated in the Southern California Children's Health Study. They reported finding an ethnic difference, with Hispanic white children having a lower prevalence of eczema than non-Hispanic white children, which could not be accounted for by sociodemographic differences.…”
mentioning
confidence: 99%